EFFORTS TO IMPROVE THE ABILITY OF CLASS I AND CLASS IV STUDENTS IN FOLLOWING THE INDEPENDENT CURRICULUM AT SDN 064976 TEMBUNG - Sani; Simamora, Septy; Manalu, Solagratia; Depina; Simbolon, Putri Alechia; Turnip, Christina (Universitas Indo Global Mandiri Palembang, 2024)
This research aims to identify the obstacles and challenges faced by class I and IV students in following the Independent Learning Curriculum at SDN 064976 Tembung, as well as finding effective strategies to improve their abilities. The research results show challenges related to limited teacher understanding, limited resources, and students' difficulty adapting. Recommended strategies include increasing teacher understanding, developing resources, and intensive mentoring for students. This research provides insight into the implementation of the Independent Curriculum in elementary schools and can be used as a basis for optimizing its implementation..